Perception of the external environment and strategic profile of the entrepreneurs of Ibirama/SC (Revista Brasileira de Contabilidade e Gestão, 2013)
So there is adherence to bold strategies of business management, we start from the assumption of the need for specific skills of the manager so that its function is exerted on the optimality of the business in the competitive market demand. The external environment which includes among others, technology, economics and politics of a society, in theory should be a prerequisite for the development of management strategies. In this perspective, there is discussion of the study that comprehensively identified the perception of the external environment and the strategic profile of entrepreneurs Ibirama / SC. The theoretical framework has allowed the elucidation of various aspects of the external environment, profile manager and strategic business. The descriptive study through a literature review, data collection also made in-situ by means of survey companies in the city limits of the City of Ibirama / SC. The data reveal that a considerable number of managers have higher education qualifications in the specific area of management and although the perception they hold of the external environment does not provide information able to develop strategies. We conclude that the perception of the external environment of the entrepreneur Ibirama / SC is negligible before its importance to the process of developing the business strategy and that the strategy profile of entrepreneurs Ibirama/SC predominantly characterized by ease of communication, negotiation creativity and innovation in general occasioning a prospector strategy and analytical modeling management.
Keywords: external environment; strategic profile; corporate strategy